Hexakis-TIPS-alkynylated nonacenes: persistent and processible [data] - Zeitter, Nico; Hippchen, Nikolai; Weidlich, Anna; Jäger, Patrick; Ludwig, Philipp; Rominger, Frank; Freudenberg, Jan; Dreuw, Andreas; Bunz, Uwe H. F. (Universität, 2023)
We prepared and characterized (UV-vis, epr, X-ray) four substituted nonacenes. They are the most stable and soluble nonacenes to date - due to six strategically placed triisopropylsilyl (TIPS)-ethynyl groups. They are stable for several weeks in the solid state. In dilute solution their half-life is 5-9 h. Crystal structure analyses of two nonacenes prove their structures. A nonacene derivative was tested in a solution-processed transistor and exhibits ambipolar charge transport (µe=0.007 cm2/Vs; µh=0.023 cm2/Vs).
Gesehen am 09.08.2023
Keywords: Forschungsdaten; Datenbank